Metabolic Analysis of the Mode of Action and Mode of Resistance for Novobiocin in Staphylococcus aureus - Weile Xie; Dan Luo; Zhe Wang (Zoonoses)
Methicillin resistant Staphylococcus aureus (MRSA) and Vancomycin resistant Staphylococcus aureus (VRSA) are critical pathogens identified by the WHO for their significant drug resistance. Targeting of bacterial gyrase, specifically the gyrB subunit, is a promising approach because of this enzyme’s essential role in bacterial DNA replication and its absence in higher eukaryotes. However, understanding of the mode of action of gyrB inhibitors remains largely incomplete. This study explored the resistance mechanisms of Staphylococcus aureus ( S. aureus ) to novobiocin, a gyrB inhibitor. Through adaptive laboratory evolution, key resistance mutations (in gyrB, potB, and fpgS) in S. aureus were identified after repeated exposure to novobiocin. Further metabolomic analysis revealed the function of the major mutation (in gyrB) in relation to the potential mechanism through which S. aureus responds to novobiocin. Through whole genome sequencing, three mutations of S. aureus in gyrB, potB, and fpgS were identified. The gyrB mutation was the primary driver of resistance, and was associated with changes in growth, survival under surface and oxidative stress, cell wall permeability, and coagulation functions. Metabolomic analysis demonstrated compensatory metabolic adjustments affecting protein synthesis and DNA replication in the resistant strain. These findings provide insights into the complex resistance mechanisms of S. aureus to novobiocin and highlight the metabolic costs associated with gyrB mutations, thereby potentially informing future antibacterial strategy development.